Development of the method for testing of efficiency criterion of models of simple target operations - Lutsenko, Igor; Vihrova, Elena; Fomovskaya, Elena; Serdiuk, Olga (Eastern-European Journal of Enterprise Technologies, 2016)
The problem of verification of indicators which are supposed to be used as criteria of efficiency of models of simple target operations is solved. For realization of such opportunity, it is offered to test the indicators on couples of reference models of simple target operations, the efficiency of which is calculated previously with the help of the developed technique and predictive indicator. Now more than one thousand indicators are developed, which the authors-developers define as efficiency indicators. As the criterion of efficiency is a global criterion of optimization, the indicator offered for the solution of optimization tasks has to provide an adequate assessment of efficiency of the optimized process in the whole range of management. This is particularly relevant for the automatic control systems. As a result of the research, it is established that the efficiency of target operations in some cases can be defined by using a method of a direct assessment of the process that is generated by the initial target operation. For this purpose, performance of a number of conditions is necessary: the studied target operation has to be simple; the compared operations have to be comparable relative to the starting investments; it is necessary to consider not only the data from the process generated by the cyclic performance of target operations, but also from the processes generated by the use of their target product. The received results allow revealing the indicators that can be used to solve the optimization problems by the criterion of efficiency. Such opportunity allows passing from a paradigm of process automation to full automation of management processes by the criterion of resource efficiency.